Benzothiazole amphiphiles promote RasGRF1‐associated dendritic spine formation in human stem cell‐derived neurons. Issue 3 (30th January 2020) - Cifelli, Jessica L.; Berg, Kyle R.; Yang, Jerry
Abstract : Synaptic dysfunction has been implicated as an early cause of cognitive decline in neurodegenerative diseases (NDDs) such as Alzheimer's disease (AD). Methods to slow down or reverse the loss of functional synapses, therefore, represent a promising avenue to explore for treating NDDs. We have previously reported the development of a class of benzothiazole amphiphiles (BAMs) that exhibited the capability to improve memory and learning both in wild‐type mice and in an AD rodent model, putatively through promoting RasGRF1‐associated formation of dendritic spines in hippocampal neurons. While these results represent a good first step in exploring a new approach to treating NDDs, the capability of these compounds to increase spine density has not been previously examined in a human neuronal model. Here, we found that neurons derived from differentiated human induced pluripotent stem cells exhibited both an increase in RasGRF1 expression and a phenotypic increase in the density of postsynaptic density protein 95‐positive puncta (which we use to provide an estimate of dendritic spine density) in BAM‐treated vs. control neurons. These results demonstrate that the previously observed spinogenic effects of BAMs in rodent neurons can be recapitulated in a human neuronal model, which further supports the potential utility of BAM agents for treating human diseases associated with spine deficits such as AD or other NDDs. Abstract : Methods to promote dendritic spine formation or prevent dendritic spines loss represent a novel approach to combat memory deficits in neurodegenerative diseases. Using induced pluripotent stem cell‐derived neurons as the first human cell model capable of evaluating dendritic spine dynamics, we show that benzothiazole amphiphiles can activate cell machinery in human neurons to promote the formation of dendritic spines.